2020
DOI: 10.4025/actascitechnol.v43i1.49854
|View full text |Cite
|
Sign up to set email alerts
|

Enterococci and Bacilli from surface water: assessment of their resistance to copper and antibiotics

Abstract: Heavy metal-resistant bacteria can be efficient bioremediators of metals and might provide an alternative method for metal removal in contaminated environments. The present study aims to isolate bacteria from the aquatic environment and evaluate their potential tolerance to copper metal, aiming at bioremediation processes. Also, compare co-resistance to heavy metal and antibiotics. The morphology of isolates was observed, and sequence analysis (16S ribosomal DNA) revealed that isolated strains were closely rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…They observed that Cr removal was through the cell membrane. Maia et al (2021) investigated the potential tolerance of Enterococcus to Cu. The results showed the maximum removal by Ent.…”
Section: Enterococcus Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…They observed that Cr removal was through the cell membrane. Maia et al (2021) investigated the potential tolerance of Enterococcus to Cu. The results showed the maximum removal by Ent.…”
Section: Enterococcus Speciesmentioning
confidence: 99%
“…Heavy metals bioremoval by using Bacillus strains has been observed and Cd reduction by B. coagulans was reported (Majlesi et al, 2017). Maia et al (2021) measured Bacillus strains ability in Cu biodegradation. The removal process was evaluated by using atomic adsorption spectroscopy.…”
Section: Bacillus Speciesmentioning
confidence: 99%
See 1 more Smart Citation